HOW GENDER DIVERSITY INFLUENCE CORPORATE SUSTAINABILITY PERFORMANCE: A LITERATURE REVIEW - RIA ANITA WIDARTI (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
The concept of sustainability is a company's ability to contribute to economic development, environmental protection and social justice and equity. Sustainability performance disclosure will improve the company's relationship with other parties, such as investors, banks, consumers, suppliers, and other stakeholders. The representation of women in the ranks of corporate decision makers provides new ideas, thoughts, perspectives, and insights related to environmental, social issues and their relationship with stakeholders (Fakir & Jusoh, 2020; Galletta et al., 2021; Gardazi et al., 2020). This study intends to discuss how gender diversity influence corporate sustainability performance with various examples from other countries and Indonesia. The result can provide a discourse for companies and further research to examine and analyze the relationship between gender diversity and corporate sustainability performance. The content analysis technique used for studi. From 251 articles grouped by keywords, 12 articles or journals have been selected according to the inclusion and exclusion criteria set. The observations period is from 2017 – 2020 through search engines and websites for journals and research articles. This study was found that 75% of the selected articles stated that gender diversity had a significant effect on corporate sustainability performance either directly or through mediation or moderating of other variables. In addition, the type of banking industry and industry with high environmental and social exposure shows the ability of women to influence sustainability performance. On the other hand, there are findings that typical, regulations and background in a country also affect the significance of gender diversity on corporate sustainability performance